Adoption of Different Sets of English Words by Serbian-Speaking Students of Technology - Smiljana M. Igrutinović; Nevena B. Banković (University of Belgrade, Teacher Education Faculty, 2024)
The aim of the paper is to examine the effect of three different groups of words on learning new vocabulary by students of English for Specific Purposes. Semantically related, thematically related, and semantically unrelated sets of words were presented to the students. After each presentation, immediate tests of receptive and productive vocabulary knowledge were performed in which the students translated words in isolation in both translation directions. Delayed testing was conducted fourteen days later and the students also answered the questions on the difficulty of each group of words and translation direction. One-way analysis of variance was used to analyze the test results. The results of immediate testing showed there was no statistically significant difference between students' receptive and productive vocabulary knowledge of the three sets of words. However, the results of the delayed test showed a significant difference in favour of the semantically related words because the students knew more words from this group compared to the thematically related and semantically unrelated groups of words. The students' attitudes are consistent with the obtained results since most of the students think that the easiest set of words for them to acquire is the semantic one. Therefore, we conclude that semantically related sets of words can be presented to the students in the classroom, although some authors claim that the semantic connection between the words hinders the acquisition of the new vocabulary.